Space debris and other threats from outer space - Pelton, Joseph N. (SpringerBriefs in Space Development, 2013)
The mounting problem of space debris in low earth orbit and its threat to the operation of application satellites has been increasingly recognized as space activities increase. The efforts of the Inter Agency Space Debris Coordinating Committee (IADC) and UN COPUS have now led to international guidelines to mitigate the creation of new debris. This book discusses the technical studies being developed for active removal processes and otherwise mitigating problems of space debris, particularly in low earth orbit. This book also considers threats to space systems and the Earth that comes from natural causes such as asteroids, coronal mass ejections, and radiation. After more than half a century of space applications and explorations, the time has come to consider ways to provide sustainability for long-term space activities.